Pengaruh Frekuensi Penggorengan Bahan Makanan Terhadap Angka Peroksida - Yunita - Nazarena; Eliza Eliza; Terati Terati; Ayu Meilina (Poltekkes Kemenkes Padang, 2022)
Evaporation of water in food during frying causes fat break down into hydroperoxides. The peroxide indicates the initial stage of oxidation. This study aims to determine the exact temperature and time of frying and the effect of frying frequency on the peroxide. The research was carried out in 2 stages, namely preliminary research aimed at getting the right temperature and cooking time, the main research aimed at getting the peroxide value of cooking oil. This study used experimental research, a completely randomized design with five treatments, two replications and deep frying. Research object: